2008
DOI: 10.1016/j.ijid.2008.05.446
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Disease Prevention: Knowledge, Attitudes, and Practices Among School Pupils in Rural Ghana

Abstract: Background: Mycoplasma can be isolated with considerable frequency from the female urogenital tracts. Ureaplasma urealyticum and Mycoplasma hominis are important genital mycoplasmas and known as sexually transmitted agents, causing mainly urethritis, pelvic inflammatory disease, spontaneous abortion, pyelonephritis, infertility, stillbirth, low birth weight, neonatal meningititis, and neonatal pneumonia. The aim of this study was to evaluate the incidence of Mycoplasma infections in women of reproductive age.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The students of grade 5 and above were relatively knowledgeable about the prevention of STIs than students of grades 1 to 4 (Table 3). This is similar to study findings from Ghana, 11,18,20 where the students’ educational level was a significant factor to have knowledge about STIs. It is true that as the education level increased, the probability of exposure to various health information sources would also be increased.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The students of grade 5 and above were relatively knowledgeable about the prevention of STIs than students of grades 1 to 4 (Table 3). This is similar to study findings from Ghana, 11,18,20 where the students’ educational level was a significant factor to have knowledge about STIs. It is true that as the education level increased, the probability of exposure to various health information sources would also be increased.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with study findings from Ghana and German. 17,18 The probable explanation for this might be students’ exposure to various information sources such as friends, media, the Internet, and books.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the National Health and Morbidity Survey (Malaysia), showed that 7.3% of the respondents whom were 13–17 years old already had sex experiences [5]. Unfortunately, during this phase many studies have proved that the youth are poorly informed about STD and its prevention [68]. According to Women Aid Organisation, women shelter home is a place which provide temporary shelter, physical and emotional support for the affected women.…”
Section: Introductionmentioning
confidence: 99%
“…There is a changing trend of sexual and reproductive behavior between young people and this need more attention and awareness by healthcare professionals to provide the necessary sexual or reproductive care and education 3 . Unfortunately, many studies during this stage have proven that young people do not have enough information about STDs and their prevention [4][5][6] . According to Women Aid Organization, women shelter home is a place which provide temporary shelter, emotional and physical support for the affected women.…”
Section: Introductionmentioning
confidence: 99%